Effectiveness of primary surgery versus primary radiotherapy on unknown primary head and neck squamous cell carcinoma: a systematic review protocol. (February 2018) - Dharmawardana, Nuwan; Campbell, Jared M.; Carney, A. Simon; Boase, Samuel
Abstract : Review question: The review question is: what is the effectiveness of primary surgery versus primary radiotherapy on disease-free survival and quality of life in adults with an unknown primary, head and neck squamous cell carcinoma?